Clinical Yield of Familial Screening After Sudden Death in Young Subjects: The French Experience. (September 2017) - Quenin, Pauline; Kyndt, Florence; Mabo, Philippe; Mansourati, Jacques; Babuty, Dominique; Thollet, Aurélie; Guyomarch, Béatrice; Redon, Richard; Barc, Julien; Schott, Jean-Jacques; Sacher, Frederic; Probst, Vincent; et al.
Abstract : Background: After sudden cardiac death with negative autopsy, clinical screening of relatives identifies a high proportion of inherited arrhythmia syndrome. However, the efficacy of this screening in families not selected by autopsy has never been assessed. We aim to investigate the value of clinical screening in relatives of all subjects who died suddenly before 45 years of age. Methods and results: One hundred and three consecutive families who experienced unexplained sudden cardiac death before 45 years of age were included from May 2009 to December 2014 in a prospective multicenter registry. Clinical screening was provided to all relatives and performed in 64 families (230 relatives, 80 unexplained sudden cardiac death). Diagnosis was established in 16 families (25%), including Brugada syndrome (7), long QT syndromes (5), dilated cardiomyopathy (2), and hypertrophic cardiomyopathy (2). The diagnostic yield was mainly dependent on the number of screened relatives (3.8±3.4 screened relatives in diagnosed families versus 2.0±1.5; P <0.005) rising to 47% with at least 3 relatives. It additionally increased from 3 of 32 (9%) to 9 of 22 (41%) when both parents were screened ( P =0.01). Diagnostic performance was also dependent on the exhaustiveness of screening (70% of complete screening in the diagnosed families versus 25%; P <0.0001) with 17 Brugada syndromes and 15 long QT syndromes diagnosed based on pharmacological tests. Conclusions: Even without autopsy, familial screening after sudden death in young patients is effective. Broad screening of relatives and systematic tests, including pharmacological challenges, greatly increases the likelihood of diagnosis in families. Abstract : Supplemental Digital Content is available in the text.